Valuing third sector sustainability organisations – qualitative contributions to systemic social transformation. Issue 1 (2nd January 2017) - Lyth, Anna; Baldwin, Claudia; Davison, Aidan; Fidelman, Pedro; Booth, Kate; Osborne, Caroline
ABSTRACT: The number and diversity of civil society or third sector sustainability organisations (TSSOs) have increased in recent decades. TSSOs play a prominent role in local approaches to sustainability. However, the contributions made by TSSOs are not fully understood, beyond a limited suite of quantifiable outputs and impacts. In this qualitative study, we examine how four TSSOs from two Australian regions, Tasmania and Queensland's Sunshine Coast, contribute to social transformation beyond discrete outputs. We examine the operation, ethos, scope and influence of these organisations over time. In so doing, we identify three common ways in which these organisations facilitate social change: by (i) enhancing social connectivity through boundary work; (ii) mobilising participatory citizenship and (iii) contributing to social learning. We conclude that TSSOs contribute significantly to the systemic social conditions that enable change for sustainability and the development of community resilience and well-being, but do so in ways undervalued by existing metrics, formal evaluation processes and funding models. Clearer recognition of, and strategic emphasis on, these qualitative contributions to social transformation is vital in ensuring that TSSOs remain viable and effective over the long term.